2020
DOI: 10.1002/jca.21831
|View full text |Cite
|
Sign up to set email alerts
|

ECP as additional immunomodulation in idiopathic hyperammonemia and recurrent hypercapnic respiratory failure early post lung transplantation

Abstract: Extra-corporeal photopheresis (ECP) is known as safe ultimate treatment option for chronic lung allograft dysfunction (CLAD). Here, we report the first case of ECP as "second-line" immunomodulatory therapy early post-transplant in an adult patient undergoing lung transplantation for severe chronic thromboembolic pulmonary hypertension, complicated by impaired consciousness due to idiopathic hyperammonemia resulting in recurrent hypercapnic respiratory failure. ECP was initiated twice weekly on post-transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Twenty‐two studies were identified, which included a total of 49 cases 1,2,4,13–15,19–32 . Individual patient‐level data varied, so denominators differ by data variable.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐two studies were identified, which included a total of 49 cases 1,2,4,13–15,19–32 . Individual patient‐level data varied, so denominators differ by data variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1,2,4,[13][14][15][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Individual patient-level data varied, so denominators differ by data variable. Mean age at time of transplant for…”
mentioning
confidence: 99%
“…This includes direct ammonia removal through renal replacement therapy, use of nitrogen scavengers, such as arginine, sodium benzoate, and sodium phenylacetate, bowel decontamination with lactulose and other oral antibiotics, and reducing enteral protein intake. Less proven modalities that have achieved some success include mitigating elevated cerebral pressures with intracerebral drain placement, extracorporeal liver support, plasmapheresis, and extra-corporeal photopheresis [38,42,46,50]. Unfortunately, these frequently failed to prevent progressive disease and death.…”
Section: Managementmentioning
confidence: 99%
“…To characterize presentation and outcomes in lung transplant recipients, we found 62 cases of hyperammonemia syndrome posttransplant with sufficient clinical details for review [1–3,7,10,12 ▪▪ ,28,33–52]. Median age was 58 years [interquartile range (IQR) 48.5–62.8 years] and 60.4% ( n = 29 out of 48) were men.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Currently, there are several pharmaceuticals on the market (e.g., Uvadex ® , Oxsoralen ® , 8-MOP ® , and Melanocyl ® ) with these active principles approved by the EMA/FDA that are used in PUVA therapy consisting of the combination of psoralens with UVA radiation. Furanocoumarin’s potential is also being evaluated for treating cancer, graft-versus-host disease and in the prevention and treatment of solid organ transplantation rejection, among others [ 16 , 17 , 18 ]. In addition to their application as pharmaceuticals, several coumarin derivatives including furanocoumarins could be used as agrochemicals due to their phytotoxic, antibacterial, antifungal, insecticide, and herbicide properties [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%